2014
DOI: 10.1200/jop.2013.001164
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the Delivery of Quality Breast Cancer Care: Initiation of Adjuvant Hormone Therapy at an Urban Safety Net Hospital

Abstract: Urgently needed interventions to reduce disparities in breast cancer treatment should take into account obstacles inherent among immigrant and indigent populations and complexities of multidisciplinary cancer care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…While some recent studies have addressed some of the previously identified weaknesses, such as addressing the psychosocial factors that may predict risk of delay [8,28], others have focused on subgroups (such as young or low income women, early breast cancer only) [23,24,29], or have not included reasons for delay [26,30,31]. It has been suggested that the patient-related interval may be influenced by a number of factors including: “demographic factors” (such as age, education); “psychological factors” (such as fear and anxiety); “social factors” (such as work and family commitments); “behavioural factors” (such as symptom recognition, awareness and watchful waiting); and “system factors” (such as access, difficulties in making appointments, distance to medical services, coordination of diagnostic tests, and inadequate communication between and within medical services) [32].…”
Section: Introductionmentioning
confidence: 99%
“…While some recent studies have addressed some of the previously identified weaknesses, such as addressing the psychosocial factors that may predict risk of delay [8,28], others have focused on subgroups (such as young or low income women, early breast cancer only) [23,24,29], or have not included reasons for delay [26,30,31]. It has been suggested that the patient-related interval may be influenced by a number of factors including: “demographic factors” (such as age, education); “psychological factors” (such as fear and anxiety); “social factors” (such as work and family commitments); “behavioural factors” (such as symptom recognition, awareness and watchful waiting); and “system factors” (such as access, difficulties in making appointments, distance to medical services, coordination of diagnostic tests, and inadequate communication between and within medical services) [32].…”
Section: Introductionmentioning
confidence: 99%
“…Initiation was higher in our study population than in Medicare-or Medicaid-insured patients, where prevalence of initiation ranges from 50% to 85%. [7][8][9][10][11][12][13][14][15] Time to initiation was also prompt, with 70% initiation within the first 12 months after diagnosis. Our results provide a more complete picture of variations in AHT use across multipayer populations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study 12 that examined whether black and Hispanic women who participated in the Women's Health Initiative were less likely than white women to report using AHT similarly found no difference in prevalence of initiation by race/ethnicity. However, some research in this area 7,9,10 suggests there are racial differences in AHT initiation and adherence, and a lower proportion of black patients receive therapy compared to whites. AHT initiation in other safety-net healthcare systems is low, 9 where black, Hispanic, and foreignborn breast cancer patients are less likely to initiate therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although transcriptional profiling of patient primary tumour tissue [ 19 ], or the 21-gene recurrence score (Oncotype Dx) for oestrogen receptor-positive, early-stage breast cancer [ 20 ], have proven utility for clinical decision-making, these tools may not always be available, affordable or used in a timely fashion in the safety net hospital setting [ 21 , 22 ]. Furthermore, the seminal study (Trial Assigning Individualized Options for Treatment or TAILORx) prospectively validating the Oncotype Dx Recurrence score in hormone receptor-positive, HER-2-negative, node-negative breast cancer, included only 7% Black patients.…”
mentioning
confidence: 99%